Organizational Commitment: Testing Two Theories - Amernic, J.; Aranya, N. (Relations industrielles / Industrial Relations, 1983)
A study of organizational commitment of professional accountants who have the chartered accountancy designation, in various occupational settings in Canada, with reference to two alternative theories of organizational commitment.